pengaruh PENGARUH PERSEPSI WAJIB PAJAK TERHADAP PENGGUNAAN ELECTRONIC FILLING PADA KPP PRATAMA JAMBI PELAYANGAN TAHUN (2019-2023): PENGARUH PERSEPSI WAJIB PAJAK TERHADAP PENGGUNAAN ELECTRONIC FILLING PADA KPP PRATAMA JAMBI PELAYANGAN TAHUN (2019-2023) - Asyifa Mutia; Ery Bestary Al Haitamy; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2025)
This research aims to examine the influence of taxpayer perceptions on the use of electronic filling in KPP Pratama Jambi Pelayangan. Electronic filing is a system for filling out and submitting tax documents electronically which is designed to make it easier for taxpayers to report their tax obligations. The research method used is a survey method using a questionnaire as a data collection instrument. The sample for this research is taxpayers registered at KPP Pratama Jambi Pelayangan. The collected data will be analyzed using regression analysis to test the relationship between taxpayer perceptions and the use of electronic filling. With better understanding, it is hoped that the effectiveness of using electronic filling in carrying out tax obligations can be increased. This research can also be a basis for developing more effective policies and strategies in increasing.